The handbook of election news coverage around the world [electronic resource] - Kaid, Lynda Lee; Streombeack, Jesper (ICA handbook series, 2009)
Focuses on the news coverage of national elections in democracies around the globe. This book brings together and compares election news coverage within a single framework, offering a consideration of